The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7189/jogh.10.020507
|View full text |Cite
|
Sign up to set email alerts
|

Screening policies, preventive measures and in-hospital infection of COVID-19 in global surgical practices

Abstract: Background In a surgical setting, COVID-19 patients may trigger in-hospital outbreaks and have worse postoperative outcomes. Despite these risks, there have been no consistent statements on surgical guidelines regarding the perioperative screening or management of COVID-19 patients, and we do not have objective global data that describe the current conditions surrounding this issue. This study aimed to clarify the current global surgical practice including COVID-19 screening, preventive measures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
1
24
0
3
Order By: Relevance
“…However, after the first wave of the pandemic, the number of cancer surgeries began to rise gradually [ 29 ]. Additionally, several studies have now reported on safe pathways to perform “non-urgent” cancer surgeries with minimal complications due to COVID-19 [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, after the first wave of the pandemic, the number of cancer surgeries began to rise gradually [ 29 ]. Additionally, several studies have now reported on safe pathways to perform “non-urgent” cancer surgeries with minimal complications due to COVID-19 [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients may potentially expose healthcare providers to the risk of contamination during surgical and anesthetic procedures [ 4 ], and positivity cases and some deaths are already occurring among health workers [ 5 , 6 ]. In this scenario, the surgical community had been pushed to rapidly understand how to deal with the virus's presence and organize the gradual resumption of surgical activity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been no consistent statements on surgical guidelines regarding the perioperative screening of COVID-19 patients. Bellato et al [2] revealed the global situation of surgical practice including COVID-19 screening, preventive measures and in-hospital infection under the COVID-19 pandemic in early April 2020 in a cross-sectional online survey of 936 centres. In 71.9% of the centres, local guidelines recommended preoperative testing based on symptoms or suspicious radiologic findings, while in 18.4% a universal testing was recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In a surgical setting, COVID-19 patients may trigger in-hospital outbreaks and have worse postoperative outcomes [1]. A large international survey captured the global surgical practice under the COVID-19 pandemic and highlighted the insufficient preoperative screening of COVID-19 in the current surgical practice [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation